Stosunek mniejszości etnicznych, narodowych i religijnych do wydarzeń Arabskiej Wiosny w Syrii - Jomma, Fuad (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2014)
Syria w porównaniu do innych państw arabskich ma skomplikowaną strukturę etniczno- religijną. Można wyróżnić: Arabów, Kurdów, Ormian, Asyryjczyków, Turkmenów oraz inne grupy etniczne. Mimo, że dominującą religią jest islam, można także zaobserwować różne odmiany chrześcijaństwa czy judaizmu. W artykule przeanalizowany zostanie wpływ konfliktu sannicko-alawickiego i jego wpływ na inne grupy etniczne i religijne w Syrii.

As compared to other Arab countries, Syria has quite a complex ethnic and religious structure. One can mention such ethnoses as Arabs, Kurds, Armenians, Assyrians, Turkmenians and more. Although Islam is the predominant religion, different types of Christianity and Judaism can also be found there. The author’s aim is to present the antagonisms between selected national and religious groups. The main issue is showing the different aspects of these groups’ involvement in the Arab Spring in Syria, for example the escalation of the conflict between the Sunnites and Alavites and its consequences for other groups. A conflict that lasts too long may increase the threat of Islamization by extremist groups. This could lead to a long-lasting crisis and destabilization of the country, which could cause a large-scale civil war as times goes by.
The Relation of Ethnic, National, and Religious Minorities to the Arab Spring in Syria
Keywords: Syria; mniejszość; etniczne; religijne; konflikt; Syria; minority; ethnic; religious; conflict